Tropical Forest Ecology and Management for the Anthropocene - González, Grizelle (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue looks forward as well as backward to best analyze the forest conservation challenges of the Caribbean. This is made possible by 75 years of research and applications by the United States Department of Agriculture, International Institute of Tropical Forestry (the Institute) of Puerto Rico. It transforms Holocene-based scientific paradigms of the tropics into Anthropocene applications and outlooks of wilderness, managed forests, and urban environments. This volume showcases how the focus of the Institute's programs is evolving to support sustainable tropical forest conservation despite uncertain conditions. The manuscripts showcased here highlight the importance of shared stewardship and a long-term, hands-on approach to conservation, research programs, and novel organizations intended to meet contemporary conservation challenges. Policies relevant to the Anthropocene, as well as the use of experiments to anticipate future responses of tropical forests to global warming, are reexamined in these pages. Urban topics include how cities can co-produce new knowledge to spark sustainable and resilient transformations. Long-term results and research applications of topics such as soil biota, migratory birds, tropical vegetation, substrate chemistry, and the tropical carbon cycle are also described in the volume. Moreover, the question of how to best use land on a tropical island is addressed. This volume is intended to be of interest to all actors involved in long-term sustainable forest management and research in light of the historical lessons and future directions that may come out of a better understanding of tropical cities and forests in the Anthropocene epoch.